PENERAPAN SIMULATOR STARTER DIRECT DRIVE BERBASIS VIDEO UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR MAHASISWA OTOMOTIF - Githa Fitri Febriyani, - (2020)
This study aims to determine the motivation and learning outcomes of students by applying a video-based simulator to the direct drive type starter system material. This research is motivated by a lack of students' understanding about the starter system material in the electrical engine course due to the absence of the supporting learning media. This causes students to be less participate during the learning process which is still focused on the lecturer (teacher-centered) because the teaching and learning activities tend to be monotonous and boring. This study used a pre-experimental method using one group pretest-posttest design research. The population in this study were students of S1 DPTM FPTK UPI batch 2018 with a total of 97 students. The sample in this study were 39 students of automotive concentration class 2018. The results of this study showed the improvement of students' motivation after learning by using a video-based starter system simulator which then obtain 44% value of motivation questionnaire. The result of students' motivation is at the "sufficiently motivated" stage. Student learning outcomes improved seen from the average value of the pretest, posttest, and T-test. The average pretest score was 42.66 and the posttest average score was 67.89. Based on the results of the T-test, it shows the value of t_countis 6.007 and df = 39-1= 38 with a significance level of 0.05 so that it is obtained t table of 1.686. t_count≥ t_table (6,007 ≥ 1,686) means that there is a significant improvement between the average of pretest and posttest results. This study proves that the use of a video-based simulator can improve the student motivation and learning outcomes. Keywords: Simulator; Starter; motivation; learning outcomes;